Horse trouble - Varner, Kristin (First Second, 2021)
Twelve-year-old Kate loves horses, but she has to take horseback riding lessons by herself because her best friend is allergic to horses. This isn't a problem, but it means she has to deal with the mean girls at the stable who bully her about her weight all on her own. To make matters worse, she's going through puberty, getting teased by her older brother and his friends, and keeps falling off her horse while riding. Kate must find a way to stand up to her bullies and get back in the saddle.